Efficacy and mechanism of poloxamine‐assisted polyplex transfection. (20th September 2013) - Zhang, Jeremy; Bae, Sooneon; Lee, Jeoung Soo; Webb, Ken
Abstract: Background: Amphiphilic block copolymers acting as biological response modifiers provide an attractive approach for improving the transfection efficiency of polycationic polymer/DNA complexes (polyplexes) by altering cellular processes crucial for efficient transgene expression. Methods: The present study aimed to investigate the effect of the poloxamine Tetronic T904, a four‐arm polyethylene oxide/polypropylene oxide block copolymer, on polyplex transfection and to determine its mechanism of action by analyzing the cellular uptake of polyplex, the nuclear localization of plasmid and RNA transcript production. Results: T904 significantly increased the transfection efficiency of polyplexes based on 25‐kDa branched polyethylenimine in a dose‐dependent manner in the presence of serum in C6 glioma cells, as well as human fibroblasts and mesenchymal stem cells. The activity of T904 was not promoter‐dependent, increasing the expression of reporter genes under both cytomegalovirus and SV40 promoters. Although T904 did not affect the internalization or nuclear uptake of plasmid, mRNA expression levels from both promoters showed dose‐dependent increases that closely paralleled increases in gene expression. Conclusions: The present study demonstrates that T904 significantly increases polyplex transfection efficiency and suggests a mechanism of increased transcriptional activity. As a four‐arm, hydroxyl‐terminated polymer, T904 is amenable to a variety of end group functionalization and covalent cross‐linking strategies that have been developed for preparing hydrogels from multi‐arm polyethylene glycol, making it particularly attractive for scaffold‐mediated gene delivery. Copyright © 2013 John Wiley & Sons, Ltd.